Fermatean Fuzzy Weighted Geometric Aggregation Operator inMultiple Attribute Group Decision Making Problems (MATEMATIKA, 2022)
Fermatean fuzzy set, an extension of Intuitionistic fuzzy set and Pythagoreanfuzzy set, plays a remarkable role in dealing with ambiguityowing to its vast spacecompared to Intuitionistic fuzzy set and Pythagorean fuzzyset. Aggregation operatorshave been helpful in multi-attribute group decision making(MAGDM) problems, becauseof their importance and efficacy in coping with uncertainty. The purpose of this paper isto prove important theorems in the domain of the Fermatean fuzzy weighted geometricoperator (FFWG) and discuss its essential properties. Mostimportantly, how to utilizethe Fermatean fuzzy weighted geometric operator in the MAGDM problem. An algorithmof the proposed method has been established. The proposed operator is applied to decisionmaking problems to show the validity, practicality and effectiveness of the new approach.The main advantage of using the FFWG method is that this method gives more accurateresults as compared to the existing methods.